An investigation of preschooler's cognitive styles on their play behavior - Parimal, Elvinna Devi (University Malaysia Sarawak, UNIMAS., 2014)
This study is an investigation of the effects of cognitive styles on preschoolers play behaviors. The study was based on previous research by Saracho N. Olivia, who indicates that cognitive styles direct the play behaviors. The methodologies used were the Play Rating Scale (PRS), and the Modified Group Embedded Figure Test (GEFT). The findings from this study showed that there is no significant relationship between cognitive styles and play behaviors. Cognitive styles do not necessarily determined the play behaviors of a child during play activities. There are significant relationship between cognitive styles and age and also between play behaviors and age. The findings also showed that there are exist differences between field dependent (FD) and field independent (FI) aged 4-, 5- and 6-year-old children's play behaviors in the physical, block, manipulative and dramatic play. Based on this study, I could conclude that cognitive styles and age are related in a way that different ages have varied types of cognitive styles. The field dependent (FD) and field independent (FI) showed different strong quality in certain play forms. Children engaged in play forms which are familiar to them and therefore this could be seen during play activities.